2017
DOI: 10.1111/cdev.12918
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Construals and Social Adjustment in Immigrant and Nonimmigrant Early Adolescents: The Moderating Role of Executive Functioning

Abstract: This study examined whether executive functions (EFs) moderate the association between independent and interdependent self-construals and social adjustment in 488 Moroccan, Romanian, and Italian preadolescents (ages 11-13) in Italy. Participants were assessed using self-report questionnaires and standardized EF tasks. Better working memory was related to increased social competence across all groups. High levels of inhibitory control were found to enhance the positive relation between interdependence and proso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 67 publications
(103 reference statements)
0
16
0
Order By: Relevance
“…The instructions were to press the key on the opposite side to where the flower was shown (incongruent block, inhibitory control). The third block (mixed block, cognitive flexibility) included randomly presented hearts and flowers, to the left or right, with the instructions to press on the same side when a heart was shown and to press on the opposite side when a flower was shown (see Miconi, Moscardino, Altoè, & Salcuni, 2019, for a detailed description of the task). Performance on the task was assessed by both accuracy (% correct responses) and reaction times (RTs) on correct trials.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The instructions were to press the key on the opposite side to where the flower was shown (incongruent block, inhibitory control). The third block (mixed block, cognitive flexibility) included randomly presented hearts and flowers, to the left or right, with the instructions to press on the same side when a heart was shown and to press on the opposite side when a flower was shown (see Miconi, Moscardino, Altoè, & Salcuni, 2019, for a detailed description of the task). Performance on the task was assessed by both accuracy (% correct responses) and reaction times (RTs) on correct trials.…”
Section: Methodsmentioning
confidence: 99%
“…For example, cognitive flexibility has recently been theorized as a crucial aspect of immigrants’ socio-emotional adjustment due to the exposure to diverse social and cultural contexts and the subsequent need to adapt one’s behaviors according to social demands (Fuligni & Tsai, 2015; Miconi, Moscardino, Altoè, & Salcuni, 2019). In contrast, preliminary findings suggest that working memory may be more independent from contextual influences than other EFs (de Abreu, Baldassi, Puglisi, & Befi-Lopes, 2013; Miconi, Moscardino, Altoè, & Salcuni, 2019). Cross-cultural differences may be magnified when comparing youth with a collectivist Chinese background to nonimmigrant Italian youth with an individualistic orientation.…”
Section: The Importance Of the Broader Cultural Contextmentioning
confidence: 99%
“…Research carried out in the last decades, mostly in countries with long and established tradition of immigration (e.g., the United States, Canada), has extensively documented the complex and multifaceted struggles and challenges faced by immigrants and their descendants. Focusing on specific ethnic minorities living in the West, most studies have shown how immigrants’ and ethnic minorities’ well-being is linked to several acculturation-specific risk and protective factors that distinguish immigrants’ experience, in accordance with their migration history, national origin, and resettlement experiences (Berry, 1997; Miconi, Moscardino, Altoè, & Salcuni, in press; Phinney, Horenczyk, Liebkind, & Vedder, 2001). Among these factors, discrimination and racism have been found to negatively affect psychological well-being among ethnic minority groups (e.g., Asian, Latino, and Black Americans; Brittian et al, 2015; Lee, 2003; Utsey, Ponterotto, Reynolds, & Cancelli, 2000).…”
mentioning
confidence: 99%
“…Participants were part of a larger study on immigrant and native Italian early adolescents’ socio-emotional adjustment (see Miconi, Moscardino, Altoè, & Salcuni, 2019). The sample included 91 Chinese early adolescents of immigrant origin (58.2% girls; 26.4% first generation, i.e., born in China) and their first-generation Chinese parents (i.e., born in China).…”
Section: Methodsmentioning
confidence: 99%